Sorghum (Sorghum bicolor) as a bean intercrop or rotation crop contributes to the survival of bean root rot pathogens and perpetuation of bean root rots - Ocimati, W.; Tusiime, Geoffrey; Opio, F.; Ugen, Michael Adrogu; Buruchara, Robin Arani (Wiley, 2017)
Root rots (RR) are the main cause of declining bean (Phaseolus vulgaris) production in southwestern Uganda. Here, beans are mainly intercropped/rotated with maize (Zea mays), sorghum (Sorghum bicolor), sweet potato (Ipomoea batatas), potatoes (Solanum tuberosum) and garden peas (Pisum sativum). These crops also suffer from RR and bean RR pathogens have been isolated from some of these crops. This study aimed to determine the extent of RR on maize, sorghum and peas, and their potential to contribute to the survival of bean RR pathogens. Therefore, experiments were carried out in bean RR‐infested farmers’ fields as well as soils inoculated with bean RR pathogens (Pythium spp. and Fusarium spp.) under screen house conditions and a susceptible bean cultivar served as a control. High RR incidence/severity scores were recorded in beans and sorghum in both farmers’ fields and screen house experiments. The high field RR incidence/severity in sorghum correlated with the screen house scores. This study shows that RR is also a problem to other crops, especially sorghum, warranting attention. The findings also imply that sorghum plays a potential role as an alternate host to bean RR pathogens, increasing inoculum density of bean RR pathogens and potentially negatively impacting the bean RR problem. Intercropping or rotating beans with sorghum in this region is not recommended. However, maize was RR‐resistant and therefore appropriate as an intercrop/rotational crop to beans in the system. A holistic rather than commodity approach is recommended for managing RR in this cropping system.